The Effects of Loneliness on Menopausal Symptoms - BAYRI BİNGÖL, FADİME; DEMİRGÖZ BAL, MELTEM (MARMARA UNIV, INST HEALTH SCIENCES, 2019)
Objectives: This study was carried out to investigate the effect of menopausal symptoms on the loneliness of women in the menopausal period. Methods: The study sample consisted of 546 women who applied to the menopause polyclinic of a state hospital in Istanbul and agreed to participate in the study. Data were collected using the Personal Information Form, UCLA Loneliness Scale and Menopausal Symptom Rating Scale (MRS). Results The mean age of the women included in the study was 52.70 +/- 6.39. The mean scores of menopausal symptoms of women included in the study; were found to be higher in women with low education level (p=0.001), women with big family structure (p=0,002) and women with low income (p=0,001). It was determined that women with less education (p=0,015), women not working (p=0,001) and women with low income (p=0,001) were found to have higher mean loneliness scores. Correlation analysis revealed that the mean scores of menopausal symptoms were increased (p=0,000) as the loneliness level average of women increased. Women with the most severe mean scores of menopausal symptoms were found to have the highest mean level of loneliness (p=0,000). Conclusion: Women with high levels of loneliness were found to have experienced severe menopausal symptoms. It was determined that as women's level of loneliness increased, menopausal symptoms increased.
Keywords: Menopause; loneliness; women's health; QUALITY-OF-LIFE; DEPRESSIVE SYMPTOMS; POSTMENOPAUSAL WOMEN; AGED WOMEN; IMPACT; PERIMENOPAUSAL; TRANSITION; MOOD